Joy for beginners - Bauermeister, Erica (G.P. Putnam's Sons, 2011)
Six women gather to celebrate their friend Kate's recovery from cancer, where she strikes a bargain with them: to celebrate her new lease on life, she'll do the one thing that's always terrified her, but if she does, each of them will also do one thing that they'd find difficult.